2021
DOI: 10.1177/00031348211041555
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Factors Contributing to Anastomotic Leak After Mid-to-High Colorectal Anastomosis

Abstract: Background Low colorectal anastomoses carry a high anastomotic leak (AL) rate (up to 20%) and thus are commonly diverted. Much less is known about mid-to-high colorectal anastomosis, which carries a leak rate of 2-4%. The objective of this study was to determine our AL rate after mid-to-high colorectal anastomosis and associated risk factors. Methods A single center retrospective cohort study of patients undergoing left colonic resections with mid-to-high colorectal anastomosis (≥7 cm from the anal verge) from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Related studies have demonstrated that BMI, an easily available and most commonly used index of obesity, is a risk factor for AL in rectal cancer patients who received anterior resection. However, other studies have reported contrary reports[ 24 , 25 ]. Considering that BMI cannot distinguish between the content and distribution of fat and skeletal muscle, it is imperative to explore whether fat and skeletal muscle content or distribution potentially impacts the development of AL.…”
Section: Discussionmentioning
confidence: 83%
“…Related studies have demonstrated that BMI, an easily available and most commonly used index of obesity, is a risk factor for AL in rectal cancer patients who received anterior resection. However, other studies have reported contrary reports[ 24 , 25 ]. Considering that BMI cannot distinguish between the content and distribution of fat and skeletal muscle, it is imperative to explore whether fat and skeletal muscle content or distribution potentially impacts the development of AL.…”
Section: Discussionmentioning
confidence: 83%